2017
DOI: 10.14701/ahbps.2017.21.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone, cholecystectomy and risk of gastric cancer

Abstract: Backgrounds/AimsThe aim of this retrospective study is to compare stomach cancer incidence, characteristics between gallstones, cholecystectomy and control groups. It also aims to investigate key variables' potential effects on overall survival.MethodsA total of 99 patients, diagnosed with stomach cancers between April 1994 and December 2015, were identified. We excluded stomach cancer patients, accrued during the first year of follow-up in both the gallstones and cholecystectomy groups, assuming that they mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…Moreover, our study is in agreement with the study from Shabanzadeh et al, to show that cholecystectomy cannot diminish the risk of prostate cancer [34]. Cholecystectomy has been shown to be capable of increasing the serum levels of cholecystokinin and secretin, and it is suggested to measure their serum levels before and after the removals of gallstones to ascertain whether this alteration is related to increased risk of prostate cancer [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our study is in agreement with the study from Shabanzadeh et al, to show that cholecystectomy cannot diminish the risk of prostate cancer [34]. Cholecystectomy has been shown to be capable of increasing the serum levels of cholecystokinin and secretin, and it is suggested to measure their serum levels before and after the removals of gallstones to ascertain whether this alteration is related to increased risk of prostate cancer [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…29 Similarly in a study of 99 patients; Kang et al, reported increased association of gall stones and cholecystectomy with stomach cancers. 30 The relationship between intra and extra hepatic cholangiocarcinoma and cholecystectomy is still not clear due to sparse literature and controversial results. In the past studies cholecystectomy was seen to be associated with decreased risk of cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were not consistent with the report showed the worse survival at the greater curvature location than lesser curvature of the gastric cancer. (32) In our study, we investigated the expression status of several tumor markers which are closely related with clinicopathologic characteristic and prognosis in GC, and are commonly used in the current clinic. But except for EGFR, none of them were found statically different expression between lesser curvature and larger curvature.…”
Section: Discussionmentioning
confidence: 99%